2018
DOI: 10.1016/j.celrep.2017.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endothelial Cells Associated with Hematopoietic Niche Formation in Humans Identifies IL-33 As an Anabolic Factor

Abstract: Bone marrow formation requires an orchestrated interplay between osteogenesis, angiogenesis, and hematopoiesis that is thought to be mediated by endothelial cells. The nature of the endothelial cells and the molecular mechanisms underlying these events remain unclear in humans. Here, we identify a subset of endoglin-expressing endothelial cells enriched in human bone marrow during fetal ontogeny and upon regeneration after chemotherapeutic injury. Comprehensive transcriptional characterization by massive paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 69 publications
2
49
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) and endothelial cells (ECs) are the two major types of cells in bone marrow niche. It has been reported that ECs provide a nutrient-rich hematopoietic niche for HSC, which can effectively promote HSC proliferation and differentiation [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) and endothelial cells (ECs) are the two major types of cells in bone marrow niche. It has been reported that ECs provide a nutrient-rich hematopoietic niche for HSC, which can effectively promote HSC proliferation and differentiation [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…(44)(45)(46) Interleukin-33 (IL-33) produced by a subset of CD105 expressing ECs in bone marrow facilitate osteogenesis and hematopoiesis. (47)…”
Section: Pattern and Diversity Of Blood Vessels In Bonementioning
confidence: 99%
“…Using mice expressing a citrine reporter in place of the Il33 gene, we found these CD169 + macrophages were the most abundant IL-33 producers in the BM (Fig. 4 D), exceeding the numbers of IL-33 + Ter119 + and CD45 − stromal cells described previously (Kenswil et al, 2018;Wei et al, 2015).…”
Section: Il-33 Is Increased In the Bm Niche With Inflammationmentioning
confidence: 63%